PERANAN KEPOLISIAN DALAM UPAYA PENCEGAHAN TINDAK PIDANA PERAMBAHAN HUTAN DI WILAYAH HUKUM KEPOLISIAN RESORT KUANTAN SINGINGI - Kurniawan, Raihan; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Forest encroachment is clearing or cutting down or regulating a forest area to be used as another area, be it plantations, agriculture, mining, etc. which is temporary or for a long time in state forest located on land which is not encumbered with illegal and illegal land rights. in accordance with the conservative rules. This type of research can be classified as a type of sociological legal research, because in this study the author directly carried out research on the legal area of the Kuantan Singing Police. Kuantan Singingi. The conclusions that can be obtained from the results of the research are first, the role of the Kuantan Singingi Police in an effort to prevent the occurrence of forest encroachment crimes has not been running optimally as expected because there is still forest destruction caused by illegal logging and the many obstacles forest ranger in overcoming illegal crimes. logging. The second obstacle in carrying out the duties of the Kuantan Singingi Police in efforts to prevent forest encroachment crimes in Kuantan Singingi is that there are no special Civil Servant Investigators in the forestry sector, the lack of facilities and the low capacity of forestry police.Keywords: Prevention-Occurrence-Crime-Forest Encroachment